2014
DOI: 10.1371/journal.pone.0100447
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Mouse Fgfr2 Mutant, Hobbyhorse (hob), Exhibits Complete XY Gonadal Sex Reversal

Abstract: The secreted molecule fibroblast growth factor 9 (FGF9) plays a critical role in testis determination in the mouse. In embryonic gonadal somatic cells it is required for maintenance of SOX9 expression, a key determinant of Sertoli cell fate. Conditional gene targeting studies have identified FGFR2 as the main gonadal receptor for FGF9 during sex determination. However, such studies can be complicated by inefficient and variable deletion of floxed alleles, depending on the choice of Cre deleter strain. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Fgf signaling functions to antagonize Wnt signaling [45]. Elimination of the expression of Fgf9 or its receptor Fgfr2 (fibroblast growth factor receptor 2), leads to upregulation of the Wnt pathway and male-to-female sex reversal [44,5254]. On the other hand, elimination of Wnt4/Rspo1/β-catenin leads to female-to-male sex reversal near birth [27,3133], suggesting that the Fgf9 and Wnt4 signaling pathways have antagonistic roles in sex determination.…”
Section: Propagation Of Fate Commitment Across the Gonad Fieldmentioning
confidence: 99%
“…Fgf signaling functions to antagonize Wnt signaling [45]. Elimination of the expression of Fgf9 or its receptor Fgfr2 (fibroblast growth factor receptor 2), leads to upregulation of the Wnt pathway and male-to-female sex reversal [44,5254]. On the other hand, elimination of Wnt4/Rspo1/β-catenin leads to female-to-male sex reversal near birth [27,3133], suggesting that the Fgf9 and Wnt4 signaling pathways have antagonistic roles in sex determination.…”
Section: Propagation Of Fate Commitment Across the Gonad Fieldmentioning
confidence: 99%
“…The instrument of choice can (a) perform protein separation (size or charge), (b) immobilize the separated protein onto the capillary wall, (c) immuno-probe the target protein using a primary and secondary antibody, (d) perform washes between antibody addition, and (e) develop, identify, and quantitate the signal ( see Fig. 1 ) Pam Sigger et al [ 4 ] used the Peggy Sue system to detect mitogen-activated protein kinase (MAPK) signaling proteins, the methods and materials of which are described below.…”
Section: Introductionmentioning
confidence: 99%
“…Knockout of Fgf9 or its receptor Fgfr2 resulted in the upregulation of Wnt4 expression and testis-to-ovary sex reversal [Colvin et al, 2001;Kim et al, 2006Kim et al, , 2007BagheriFam et al, 2008;Siggers et al, 2014]. Similarly, partial ovary-to-testis sex reversal was observed when Wnt4 [Vainio et al, 1999;Jeays-Ward et al, 2003], Rspo1 [Chassot et al, 2008;Tomizuka et al, 2008], or β-catenin [Manuylov et al, 2008;Liu et al, 2009] was ablated.…”
Section: Cross-talk Between the Testicular And Ovarian Pathway Of Genmentioning
confidence: 99%
“…1 C). Mice homozygous for a null mutation in Fgf9 or Fgfr2 exhibit male-to-female sex reversal, with all testis-specific cellular events being disrupted, including cell proliferation, mesonephric cell migration, Sertoli cell differentiation, and testis cord formation [Colvin et al, 2001;Kim et al, 2007;Bagheri-Fam et al, 2008;Siggers et al, 2014]. Accordingly, mutations in FGFR2 in human have been identified that result in 46,XY DSD [Bagheri-Fam et al, 2015].…”
Section: Control Of Testis Developmentmentioning
confidence: 99%